Conserving Indonesia's nature and culture through empowerment of indegenous technology in creative industry SMEs - Elzavira Felaza (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
Nature and culture are both unique potential that Indonesia can promote to face the global market. Small and Medium Enterprises (SMEs) gives big contribution to Indonesia's Gross Domestic Product (GDP). One of the most contributing kinds is batik fashion design creative industry SME. Indonesian batik is a masterpiece of cultural heritage in humanity. Natural dyes batik industry brings major impact to economy and environment. Eco-friendly batik SME that utilise natural resources is one of the ways of conserving nature and culture. This paper would provide an environmental approach of analysing indigenous technology used to produce batik and the natural dyes involved. To achieve the goals, case study and SWOT analysis will be used. The outputs of this paper are to collect information and suggest optimisation of indigenous technology in order to conserve nature, culture and preparing Indonesia for the AFTA and AEC.
Keywords: 650; batik fashion design creative industry SME; natural dyes; indigenous technology